Colloidal stability of Fe3O4 magnetic nanoparticles differentially impacted by dissolved organic matter and cations in synthetic and naturally-occurred environmental waters. (October 2018) - Wang, Hao; Zhao, Xiaoli; Han, Xuejiao; Tang, Zhi; Song, Fanhao; Zhang, Shaoyang; Zhu, Yuanrong; Guo, Wenjing; He, Zhongqi; Guo, Qingwei; Wu, Fengchang; Meng, Xiaoguang; et al.
Abstract: Better understanding of the colloidal behaviors of nanomaterials impacted by aquatic chemistry parameters is needed for appropriate evaluation of the environmental risks posed by nanomaterials in natural waters. In the study, the colloidal stability of Fe3 O4 magnetic nanoparticles (Fe-MNPs) was evaluated over a range of chemistry characteristics [e.g., pH, dissolved organic matter (DOM), salt types, cationic strength] in six synthetic water samples. The findings from the synthetic water samples were further examined with eight "real world" environmental water samples. Our results demonstrated that DOM fraction, humic acid (HA), promoted suspension of Fe-MNPs more by hydrophobic interactions in addition to ligand exchange and electrostatic effects compared with fulvic acid (FA). Capability of cations to increase aggregation of Fe-MNPs were in the order of Ca 2+  > Mg 2+ >> Na + because of their different degrees of bridging complexation with DOM molecules on particle surfaces. As a key parameter for indicating Fe-MNPs colloidal stability, Zeta (ζ) potentials of Fe-MNPs in these waters samples were well correlated to (R 2  = 0.880, P  < 0.001) the contents, types and adsorption forms of DOM and cations. However, several other factors could also affect the hydrodynamic diameter (HDD) of Fe-MNPs in the "real world" environmental waters. It assumed that ampholytic-DOM molecules such as amino acid- and protein-like molecules caused great aggregation of Fe-MNPs. These findings would be helpful for better understanding and evaluating the colloidal behaviors of nanomaterials when they released into natural water environment, thus could shed light on developing relevant pollution control strategies. Graphical abstract: Highlights: Impacts of DOM and cations on colloidal stability of Fe-MNPs evaluated in synthetic waters. Differential impacts by DOM and cations further verified by naturally-occurred environmental water samples. Cations promoted multilayer adsorption of DOM on Fe-MNPs by bridging complexation effects. Ligand exchange and hydrophobic interactions of DOM affected stability of dispersed Fe-MNPs. Abstract : The colloid stability of Fe-MNPs in environmental waters was affected by bridging complexation of cations with DOM molecules as well as adsorptions of amino acid- and protein-like molecules on the particle surface.